Effect Of Imports, Industrial Sector, And Service Sector On Value-Added Tax With Regulatory Quality As A Moderating Variable - Yuninda Anggraini Putri; Suparna Wijaya (Educoretax, 2023)
State revenue to organize its government is mostly collected by taxation as the main source. In its implementation, taxes are imposed directly and indirectly. The indirect tax that plays a role in the structure of state revenue is Value Added Tax (VAT). VAT is imposed on goods or services consumed in an area based on a set rate. VAT imposition of the highest rates on average is imposed in European countries. There are 11 European countries with the highest VAT rates, which are the object of research, namely Hungary, Croatia, Denmark, Norway, Sweden, Greece, Iceland, Finland, Ireland, Poland, and Portugal. This study will discuss the effect of value added on the industrial and service sectors, which are the main sectors in the 11 countries as well as the effect of international trade activities, namely imports, on VAT revenues with a moderation of the regulatory quality index. The results show that the imported variable and the added value of the industrial and service sectors, both before and after interaction with the moderating variable of the regulatory quality index, significantly influence VAT acceptance. For the partial results, before moderation with the regulatory quality index, imports don't significantly affect VAT revenue. In contrast, the industrial and service sectors have significant negative effects on VAT revenue. Furthermore, after interacting with regulatory quality variables, imports, value added in the industrial and service sectors have a significant positive influence on VAT revenue. This shows that the moderating variable of the regulatory quality index plays a role in strengthening the relationship between the independent and dependent variables.